Survey on the level of satisfaction towards the technical services department of Mesiniaga Sdn Bhd / Soberi Salleh and Noraini Mohamad - Soberi, Salleh; Noraini, Mohamad (Faculty of Business and Management, 1984)
The "Information Product", was a division in International Business Machines (IBM) Malaysia. Since its incorporation as Mesiniaga Sdn Bhd in January 1982, there have not been any feasibility study on the efficiency of the Technical Service Department and survey to find out ahoutv.customer satisfaction. The scope of "Survey on the Level of Satisfaction toward the Technical Service Department of Mesiniaga Sdn Bhd" has been limited to the Technical Service Management aspect. The financial or the organizational aspect of the company will not be considered.The target audience of the survey are the user of the IBM electric typewriter and the purchasing manager in government and commercial organizations which have their machines under Service Agreement with Mesiniaga Sdn Bhd.Area of research on the survey was carried out in Petaling Jaya and Kuala Lumpur. Various methods were employed to collect the relevant information to enable to determine the effectiveness and the reliability of the survey. Desk research includes all analysing of available data, statistic, published and unpublished information related to the subjects.